RISKS OF SELF-MEDICATION AND THE IMPORTANCE OF CONTROLLED DRUG SALES (REMUNOM, 2025)
Self-medication is the act of taking medications on your own. The complexity of selfmedication in the Brazilian social routine evidenced a concern with the theme and discussion to articulate the relationship with health. In this perspective, this study concludes the theme of self-medication: influence of drug advertising on self-medication in Brazil. This is a narrative bibliographic review about the legal process for establishing the norms of supervision, indiscriminate use of medications and the influence of advertisements and the performance of the pharmacist professional, based on the review of National literature. The analyses allowed us to know the historical trajectory of the legislation, the consequences of the irrational use of medications and the strong influence of marketing as well as the need for professional supervision and performance in a broader way. In this regard, it is important to highlight the fragility of the state agencies responsible for the control of advertisements, the strength of large industrial corporations, the lack of information from society about the use of medicines and the importance of the pharmacist in Consumer orientation.